Globalism and the pursuit of authenticity: The making of diasporic public sphere in Singapore - Harper, T. N. (Sojourn, 1997)
According to the author, Singapore is a child of diaspora. Its history embodies many of the tensions of blood and belonging that the concept of diaspora evokes. He explores the role of diaspora in the history of colonial Singapore, the creation of the intellectual culture that embodies both the demands of globalism and the desire for authenticity. (DÜI-Sen)